Behaviour as an indicator of cyclic trends in abundance of Canada lynx (Lynx canadensis) and snowshoe hare (Lepus americanus) - Shannon M. Crowley; Chris J. Johnson; Dexter P. Hodder (Ecological Indicators)
Changes in reproduction may be closely linked to population density and often manifest in various behaviours. Thus, variation in behaviours associated with reproduction can provide insights into the mechanisms influencing the distribution and abundance of populations as well as broader community dynamics. We used a combination of occurrence and behavioural data from camera traps to measure variation in the abundance of Canada lynx during two time periods with contrasting abundance of their primary prey, snowshoe hare. Our first objective was to determine if N-mixture models, camera occurrence rates, and behaviours could be used to monitor trends in cyclic abundance. Our second objective was to investigate the underlying environmental and ecological factors influencing lynx reproductive behaviours (cheek-rubbing, scent-marking, and grouping). We found that lynx behaviours and relative abundance were correlated among years and that those relationships varied with the abundance of snowshoe hare. Consistent with our predictions, years with greater abundance of lynx and hare were characterized by increases in cheek-rubbing, scent-marking, and grouping behaviours. Variation in behaviour and estimates of abundance proved to be strong co-occurring indicators of the cyclic population dynamics of Canada lynx. Behaviour can provide valuable insights into the mechanisms (i.e., prey availability, breeding activity) that influence population distributions and abundance.